Analisis Sikap Konsumen dan Motivasi Konsumen Dalam Minat Menggunakan E-Wallet Sebagai Alternatif Pembayaran Masa Depan - Indah Lestari; Pristiyono Pristiyono; Abd. Halim (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2023)
The development of technology can provide assistance and convenience for the development of departmental activities, commercial and economic activities. This is certainly due to the development of online transactions which is increasing rapidly resulting in a variety of new technologies in the financial aspect, for example, e-wallets. The purpose of this study is specifically to find out the factors that influence the interest of e-wallet users in society, specifically what is meant is to choose consumer attitudes and consumer motivation as independent variables, where through consumer attitudes and consumer motivation in the interest of e-wallet users will be a way to solve the problems faced. This type of approach uses an explanatory research approach and the author sets as many as 100 respondents who meet the requirements and purposive sampling techniques with data collection techniques using primary data (questionnaires) using google form. The scale technique used is a Likert scale with a statement that has five alternative choices as answers, namely strongly agree, agree, disagree, strongly disagree, disagree less. The data analysis technique that will be used in this study is Smart PLS v 4.0. The results of this study concluded that consumer attitudes partially have an influence on e-wallet user interest. Consumer motivation partially has an influence on the interest of e-wallet users